KAJIAN HUKUM ISLAM TERHADAP PERNIKAHAN SESAMA JENIS DI ERA MILINEAL - Abd. Rahmad, Joni Zulhendra dan (Normative Jurnal Ilmiah Hukum, 2023)
This same-sex marriage arises as a result of sexual orientation that deviates from normal human sexual orientation. This deviant sexual orientation belongs to a sex abnormality called homosexual (gay and lesbian). Meanwhile, a normal sexual orientation is called heterosexual (a sense of attraction and love for different sexes, male and female). Even though the sexual urge is something natural, Islam does not allow its fulfillment to take place without rules. Islam stipulates that sexual urges must be channeled in marriage, not by prostitution and having a mistress or husband. The ideal marriage is one that can maintain self-respect (husband, wife and children) and provides peace based on love and affection. sexual behavior from homosexual groups and same-sex marriages is unlawful, the prohibition regarding this is clearly stated in the Qur'an and hadith. There are various interpretations and opinions regarding the punishment for those who do it, but the levels are being killed, punished and given an education.